2010
DOI: 10.1109/tip.2010.2050625
|View full text |Cite
|
Sign up to set email alerts
|

Image Super-Resolution Via Sparse Representation

Abstract: This paper presents a new approach to single-image super-resolution, based on sparse signal representation. Research on image statistics suggests that image patches can be well-represented as a sparse linear combination of elements from an appropriately chosen over-complete dictionary. Inspired by this observation, we seek a sparse representation for each patch of the low-resolution input, and then use the coefficients of this representation to generate the high-resolution output. Theoretical results from comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
653
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 4,415 publications
(656 citation statements)
references
References 25 publications
2
653
0
1
Order By: Relevance
“…It was also compared with promising reconstruction methods that employ wavelet transform (WT), such as Wavelet Zero Padding (WZP) [31] and Demirel-Anbarjafari Super Resolution (DASR) [12]. Finally, the proposed SR-WAFE-SR technique was compared with state-of-the-art learning methods that use sparse representation and CNN such as Super-Resolution with Sparse Mixing Estimators (SME) of Mallat et al [15], the Sparse coding of Yang et al (ScSR) [14], Beta Process Join Dictionary Learning (BP-JDL) of He [16], and the Super-Resolution Convolutional Neural Network (SRCNN) of Dong et al [20].…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also compared with promising reconstruction methods that employ wavelet transform (WT), such as Wavelet Zero Padding (WZP) [31] and Demirel-Anbarjafari Super Resolution (DASR) [12]. Finally, the proposed SR-WAFE-SR technique was compared with state-of-the-art learning methods that use sparse representation and CNN such as Super-Resolution with Sparse Mixing Estimators (SME) of Mallat et al [15], the Sparse coding of Yang et al (ScSR) [14], Beta Process Join Dictionary Learning (BP-JDL) of He [16], and the Super-Resolution Convolutional Neural Network (SRCNN) of Dong et al [20].…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…69). These images were obtained from the code provided by Yang et al [14] and Zeyde et al [23]. In this database, all the images are treated as HR images and the LR version is obtained by using the down-sampling operator and the blurring filter as follows:…”
Section: Dictionary Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as SAR images contain rich feature information, an ideal de-noising result can hardly be realized if only by limited orthogonal transform, which cannot represent all the image features. The recent development of sparse representation has led to its widespread use in image processing, such as super-resolution reconstruction [11], edge detection [12], and face recognition [13]. The image de-noising method based on sparse representation of dictionary learning is applied to suppress the speckle of SAR images in [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The key idea of these methods is to utilize the relationship between the high-resolution (HR) and the LR images, learned via training images, to help recover details in the target LR images. Freeman et al [2], Chang et al [3], and Yang et al [4] showed that state-of-the-art performance can be achieved by using various learning-based methods. The major limitation of these methods is that a significant amount of HR images are required for learning.…”
Section: Introductionmentioning
confidence: 99%